Citizen Oversight of Presidential Performance. Issue 2 (13th May 2016) - Buchanan, Bruce
Abstract : Presidential oversight is a core citizen duty, yet competence is rarely assessed. I use 855 interviews conducted during the final Bush and initial Obama terms to test a novel citizen oversight assessment tool: a classification matrix created by juxtaposing historically important presidential assessment values (effectiveness, morality, and prudence) against equally familiar evaluative "targets" (presidential traits, actions, and results). Eighty‐one percent of mentioned evaluative criteria fit the matrix, establishing its construct validity and enabling meaningful assessment of citizen competence. The yield is (1) a cross‐time record of how Americans judge presidents and (2) new findings concerning the comparative importance of presidential results and actions, citizen sensitivity to presidential differences, and the worrisome rise of partisanship.